2016
DOI: 10.1128/aac.00682-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tedizolid in Morbidly Obese and Covariate-Matched Nonobese Adults

Abstract: Tedizolid is a novel oxazolidinone antimicrobial administered in its prodrug form, tedizolid phosphate, as a fixed once-daily dose. The pharmacokinetics of tedizolid has been studied in a relatively small proportion of morbidly obese (body mass index [BMI] of >40 kg/m 2 ) adults through population analyses with sparse sampling. The current study compared the intensively sampled plasma pharmacokinetics of tedizolid phosphate and tedizolid in 9 morbidly obese and 9 age-, sex-, and ideal body weight-matched nonob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Pooled analyses of phase III studies showed a numerical, but nonsignificant, decrease in clinical response rates with increasing BMIs. 70 No dose adjustments for tedizolid are expected for obesity based on two analyses showing similar PK profiles (AUC, Vd, Cl, and C max ) in obese versus nonobese healthy adults and those with skin and skin structure infections. 70,71 Summary Oxazolidinones do not appear to require dose adjustments in obesity.…”
Section: Tedizolidmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled analyses of phase III studies showed a numerical, but nonsignificant, decrease in clinical response rates with increasing BMIs. 70 No dose adjustments for tedizolid are expected for obesity based on two analyses showing similar PK profiles (AUC, Vd, Cl, and C max ) in obese versus nonobese healthy adults and those with skin and skin structure infections. 70,71 Summary Oxazolidinones do not appear to require dose adjustments in obesity.…”
Section: Tedizolidmentioning
confidence: 99%
“…70 No dose adjustments for tedizolid are expected for obesity based on two analyses showing similar PK profiles (AUC, Vd, Cl, and C max ) in obese versus nonobese healthy adults and those with skin and skin structure infections. 70,71 Summary Oxazolidinones do not appear to require dose adjustments in obesity. Data are insufficient at this time to recommend alternative linezolid dosing strategies (e.g., continuous infusions) in obese populations but should be studied in higher degrees of obesity (e.g., above 150 kg), for the treatment of VAP and those with concomitant critical illness.…”
Section: Tedizolidmentioning
confidence: 99%
“…Further evidence is provided by a recently published study demonstrating that the PK exposure was similar (ß20% lower) in morbidly obese (BMI ࣙ 40 kg/m 2 ) and in nonobese subjects, although it should be noted that this was a small-scale study with just 9 subjects per group. 25 In the 2 phase 3 studies of tedizolid in patients with ABSSSIs, the early clinical response at 48 to 72 hours declined with increasing BMI in tedizolid-treated patients. 26 However, by the posttherapy evaluation, investigator-assessed clinical success rates were similar for patients with BMI < 30 and ࣙ 30 kg/m 2 (94.6% and 91.1%, respectively) and were slightly lower for the group with BMI ࣙ 35 kg/m 2 (86.0%; data on file).…”
Section: Discussionmentioning
confidence: 99%
“…76 A recent independent study confirmed that the tedizolid plasma PK profile is not significantly different in morbidly obese subjects compared with age-, sex-, and IBW-matched nonobese subjects. 77 These findings are relevant because lower numerical but nonsignificant trends in response rates were observed as a function of increasing BMI category in the pooled analyses of Phase III studies of tedizolid. 78 Despite these trends, insufficient evidence currently exists to recommend a higher daily dose of tedizolid in obese patients.…”
Section: Tedizolidmentioning
confidence: 92%